SOCIAL SPACE AS A CONDITION OF MEMORY IN THE DEVELOPMENT OF HUMAN ACTIVITY - Oleg Maltsev (Освітній дискурс, 2020)
If the object of our work is social space, its modalities and species characteristics, the subject is theoretical models that represent the role of mechanisms of memory in social space. The article is aimed to study the phenomenon of memory in social space and assumes the study of memory in the interaction with external environment. The shown result is reflection of the outcomes of systematization of knowledge about the relationship between mechanisms of memory and the phenomenon of formation of social space, which are the result of philosophical reflection on the principles of work of blocks of human memory.